Virtue-Based Morality: Not Virtue Ethics - Gorga, Carmine (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
Morality is the daily pursuit of moral actions whose sum total results in the achievement of the moral life. It is not easy to live a moral life. That is why we need practice, practice. And much forgiveness of ourselves and others. We must constantly be on our guard against self-deceit. Our self-interest, our shortsightedness, our ignorance can easily lead us astray. A double and triple judgment from other people might help. It usually does. The moral action is the action that is prudent, just, courageous, temperate, wise, true, and full of understanding, hope, faith, and love. The moral action is not in response to a static morality, but a morality that is creative and vital, a morality in action that responds to the changing needs of the moment, a morality that stays as far away as possible from vices. We have to become responsible people in all our words and actions. After identifying who the sworn enemies of morality are, this paper will concentrate its attention on three aspects of the overall field: 1. The number of the virtues; 2. The functions that the virtues perform; and 3. The reasons for the universal (?) condemnation of vices.